Pattern and determinants of self-medication among pregnant women attending antenatal clinics in primary health care facilities in Ogbomoso, Oyo State, Nigeria - Olaniyan Akintunde Babatunde; Ikeola Adejoke Adeoye; Aishat Bukola Usman; Chukwuma David Umeokonkwo; Olufunmilayo Ibitola Fawole (Journal of Interventional Epidemiology and Public Health)
Introduction: Self medication in pregnancy has continued to be on the front burner of the global public health discourse due to the increased incidence of abortion, foetal malformation and antimicrobial resistance that were found to be associated with it. Inspite of this burden, in Nigeria, most studies on self-medication were conducted on the general population with only a few carried out among pregnant women. Therefore, this study was carried out to determine the prevalence and factors associated with self-medication among pregnant women in Oyo State.